1999
DOI: 10.1159/000017179
|View full text |Cite
|
Sign up to set email alerts
|

Delirium: Effectiveness of Systematic Interventions

Abstract: The purpose of this paper was to review evidence related to the effectiveness of systematic interventions in preventing or detecting and treating delirium. The review process involved a systematic search of the literature on each topic, assessment of the validity of the studies retrieved and examination of their results. The literature search identified 10 studies on prevention and 7 studies on detection and treatment. A broad spectrum of systematic interventions appeared to be modestly effective in preventing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 21 publications
(28 reference statements)
0
21
0
1
Order By: Relevance
“…Searches on systematic reviews identified 3178 papers, including 2099 articles in Medline, 334 articles in PsychINFO, 724 articles in the Web of Knowledge, and 21 articles in the Cochrane Library. Sixteen systematic reviews [7,12,[30][31][32][33][34][35][36][37][38][39][40][41][42][43] were found in Medline, one in the Web of Knowledge [44], one in EMBASE, [45] and one in the Cochrane Library [46]. No additional systematic review was found in PsychINFO.…”
Section: Results Of Literature Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…Searches on systematic reviews identified 3178 papers, including 2099 articles in Medline, 334 articles in PsychINFO, 724 articles in the Web of Knowledge, and 21 articles in the Cochrane Library. Sixteen systematic reviews [7,12,[30][31][32][33][34][35][36][37][38][39][40][41][42][43] were found in Medline, one in the Web of Knowledge [44], one in EMBASE, [45] and one in the Cochrane Library [46]. No additional systematic review was found in PsychINFO.…”
Section: Results Of Literature Searchmentioning
confidence: 99%
“…These interventions should be considered for all delirious patients. Specific therapeutic interventions and nursedirected care seem to have a beneficial effect on the evolution of delirium in surgical [7,44,47] and medical [5,51,88,89,114] inpatients.…”
Section: Investigation and Treatmentmentioning
confidence: 99%
“…This justifies a systematic approach to its detection, prevention, pharmacological and non-pharmacological management [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…The risk factors encompass primary risk factors (i.e., brain damage, dementia, and cognitive impairment due to stroke) (Barr et al, 2013;Michaud et al, 2007), physical factors (i.e., visual and auditory disorders, fluid and electrolyte imbalance, metabolism disorders, emergency hospitalization, hypoperfusion, pain, fracture, hypertension, alcoholism, high severity of illness at admission, and infection) (Barr et al, 2013;Cole, 1999;Sendelbach et al, 2009), and frequently, combinations of several factors (i.e., combination of sleep deprivation, use of a restraint, and exposure to noise) (Michaud et al, 2007). Therefore, a multidisciplinary and multi-component intervention approach is recommended for delirium prevention (Boorsma et al, 2011;Cerejeira and Mukaetova-Ladinska, 2011;Holroyd-Leduc et al, 2010).…”
Section: Introductionmentioning
confidence: 99%